Some thoughts on teaching methods in gynecology. - Valdivia Ponce, Oscar (2015)
My purpose is therefore to present some thoughts on the methodology of teaching in gynecology, which can be valid for medical education in general and for any particular specialty. The study of the methodology of teaching in gynecology is a complicated issue that involves the knowledge of teaching and learning in their objectives, content, in teacher-deponent relationship and structure of the socio-cultural reality of the country in which it operates.